History and development of education in Tanzania - Mushi, Philemon Andrew K. (Dar es Salaam University Press, 2009)
In History and Development of Education in Tanzania, Philemon A.K. Mushi, examines the historical development of education in Tanzania, from the pre-colonial to post-independence periods, delineating the economic and social context which shaped and helped to define the origins of various education reforms in formal and non-formal education and their developments in Tanzania beyond 1990. The book has attempted to uncover the underlying context with which the various education reforms were conceived and originated. At the same time, analysis of the current provision of education has been made to determine the challenges facing education provision in the country. -- Provided by publisher